All-fiber ytterbium doped Q-switched fiber laser based on copper nanoparticles saturable absorber - Muhammad, Ahmad Razif; Yasin, Moh; Ahmad, Mushtaq T.; Zakaria, Rozalina; Rahim, Hazli Rafis Abdul; Jusoh, Zulzilawati; Arof, Hamzah; Harun, Sulaiman Wadi (National Institute R & D of Materials Physics, 2018)
The Q-switching pulses generation in an Ytterbium-doped fiber laser (YDFL) passively Qswitched by a copper nanoparticles (CuNP) based saturable absorber (SA) was experimentally demonstrated. The high-quality SA with a modulation depth of 36% was fabricated by depositing nano-sized particles of Cu layer onto the surface of polyvinyl alcohol (PVA) film through the thermal evaporation process. By inserting the SA into a YDFL cavity, stable Q-switched operation was achieved with the maximum pulse energy up to 7.48 nJ, the shortest pulse width of 3.89 µs and pulse repetition rates varying from 41 to 104 kHz. These results suggested that CuNP could be developed as an effective SA for pulsed laser operation at 1 µm.